Edukasi Kepemimpinan Berbasis Tradisi Lokal pada Masyarakat Tolaki di Kabupaten Konawe - Nur Alim; Badarwan Badarwan; Syahrul Syahrul (Institut Agama Islam Negeri (IAIN) Kendari, 2020)
This article aims to explore the education of local culture-based leadership in the Tolaki community, which includes: 1) the origins of Tolaki culture; 2) the noble values shared by the Tolaki people; 3) Pu'utobu as an actor in the traditional leadership practices of the Tolaki people; 4) Tolaki's culture-based leadership education process. To explore these four aspects, a qualitative approach with ethnographic methods is used. Data collection uses in-depth interview techniques, involved observations, and document studies. The collected data is analyzed through domain analysis, taxonomic analysis, componential analysis, and cultural theme analysis. To guarantee the validity of the data, an extension of observation is carried out, increased perseverance, and triangulation. The results showed that Tolaki culture has a closeness to cultures in Indonesia, both because of its origins and cultural contact. Therefore Tolaki culture contains noble values that are universal, can be accepted and practiced by various groups of people. In the context of leadership, traditional leadership practices are played by Pu'utobu, in customary matters. The challenge is that the traditional leadership education of the Tolaki people is not well institutionalized.Keywords: Traditional Leadership Education, Tolaki Culture